Typologies of Canadian young adults who drive after cannabis use: A two‐step cluster analysis. (20th April 2022) - Huỳnh, Christophe; Beaulieu‐Thibodeau, Alexis; Fallu, Jean‐Sébastien; Bergeron, Jacques; Jacques, Alain; Brochu, Serge
Abstract: Young adults that drive after cannabis use (DACU) may not share all the same characteristics. This study aimed to identify typologies of Canadians who engage in DACU. About 910 cannabis users with a driver's license (17–35 years old) who have engaged in DACU completed an online questionnaire. Two‐step cluster analysis identified four subgroups, based on driving‐related behaviors, cannabis use and related problems, and psychological distress. Complementary comparative analysis among the identified subgroups was performed as external validation. The identified subgroups were: (1) frequent cannabis users who regularly DACU; (2) individuals with generalized deviance with diverse risky road behaviors and high levels of psychological distress; (3) alcohol and drug‐impaired drivers who were also heavy frequent drinkers; and (4) well‐adjusted youths with mild depressive‐anxious symptoms. Individuals who engaged in DACU were not a homogenous group. When required, prevention and treatment need to be tailored according to the different profiles.